Job motivation and associated factors among healthcare professionals serving in primary hospitals in the Central Gondar Zone, Northwest Ethiopia: a mixed-methods approach - Legesse, Mandefro Tadesse; Abuhay, Habtamu Wagnew; Worku, Nigusu; Dellie, Endalkachew (Frontiers in Public Health, 2025)
BackgroundLow performance in health facilities is associated mostly with poor healthcare worker motivation in the workplace, and this burden is dominant in developing countries such as Ethiopia. Therefore, this study aimed to assess job motivation and associated factors among healthcare professionals in Central Gondar Zone primary hospitals in Northwest Ethiopia.MethodsAn institutionally based cross-sectional study with a qualitative component was conducted at Central Gondar Administrative Zone primary hospitals in the Amhara National Regional State, Ethiopia. A total of 396 healthcare professionals with more than six months of experience at primary hospitals in the Central Gondar Zone participated. Multiple logistic regression was fitted, and Odds ratio (OR) with 95% CIs was used to measure the strength of associations and variables with a p-value of <0.05 were considered significantly associated with the outcome. Thematic analysis was performed for the qualitative part.ResultsA total of 41.81% of healthcare professionals with a 95% Cl [36.9, 46.6] had good job motivation. A degree of educational level (AOR = 1.84, 95% CI [1.178, 2.874]), being satisfied with training opportunities (AOR = 1.92, 95% CI [1.201, 3.083]), and having a written job description (AOR = 2.58, 95% CI [1.497, 4.460]) were significantly associated with job motivations.ConclusionHealthcare professionals’ job motivation status was relatively low. In addition, having a degree in educational level, being satisfied with training opportunities, and having a written job description were significant positive predictors of good job motivation. Additionally, the thematic analysis of qualitative data identified both short- and long-term training opportunities and the lack of clear, updated job descriptions, both of which significantly impacted job motivation.